Perlindungan Hukum Terhadap Pekerja Pada Perjanjian Kerja Waktu Tertentu (PKWT) Dalam Hal Pemberian Uang Kompensasi Setelah Berakhirnya Kontrak - Amelia Putri Permata Sari; Engrina Fauzi (GLOBAL SCIENTS PUBLISHER, 2025)
PKWT (Fixed Term Employment Agreement) workers are non-permanent employees who are employed with an employment agreement that has a certain duration or period. PKWT is often used for temporary or project-based work. PKWT employees are entitled to compensation money as a replacement for rights after the employment agreement is completed. Protectionifor PKWT workers has not been specifically regulated, although there are general provisions in the Manpower Law regardingitermination of employment, problems often arise such as lower salaries and cases of termination of employment (PHK) before the contract ends, compensation money not given by employers which is detrimental to workers. The government provides legal protection to workers both preventively and repressively, through the formation of laws and regulations and the implementation of systematic supervision. The focus of this study is to analyze the form of legal protection for workers with the status of a Fixed Term Employment Agreement (PKWT), especially regarding the right to compensation after the employment contract ends. The Job Creation Law and its implementing regulations are a form of protection for workers' fundamental rights that are adjusted to the dynamics of employment developments. This study uses a normative legal research method, by analyzing primary and secondary legal materials through a statutory, conceptual, and case study approach. The results of the study show that if the employment relationship ends before the PKWT period is over, the employer is still obliged to pay compensation to the worker,iwith the amount calculated based on the period of work that has been undertaken. Fulfillment of basic workers' rights is the responsibility of the employer and requires active government involvement, both in the form of regulation and supervision. The conclusion of this study confirms that legal protection for PKWT workers in terms of providing compensation after the contract ends has been regulated and guaranteed by the government, referring to the provisions of Article 61A of the Job Creation Law and Articles 15, 16, and 17 of Government RegulationiNumber 35 of 2021 concerning the provision of compensation for PKWT workers.